Infrastructure-360: Analyzing the Performance of the Infrastructure Sector from Multiple Sides - Helmi Adam; Noer Azam Achsani; Roy H.M. Sembel; Linda Karlina Sari (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The infrastructure sector serves as the backbone of national economic growth, with both state-owned enterprises (SOEs) and non-state-owned enterprises (Non-SOEs) playing strategic roles in public service delivery and investment. However, the Covid-19 pandemic has disrupted the sector's stability and performance, highlighting the need for a more comprehensive analysis of the internal and external factors influencing company performance across different periods. This study aims to examine the impact of corporate fundamentals, macroeconomic indicators, the Indonesia Composite Index (ICI), and Environmental, Social, and Governance (ESG) factors on the profitability and stock returns of SOEs and Non-SOEs in the infrastructure sector before, during, and after the Covid-19 pandemic. Using a descriptive quantitative approach and quarterly financial data from 2018 to 2023 for 42 companies, the study finds that SOEs demonstrate greater financial stability, while Non-SOEs exhibit higher operational adaptability. ESG-implementing firms generally report better profitability and healthier capital structures, albeit with higher volatility. These findings suggest the importance of enhancing operational efficiency, reinforcing ESG adoption, and maintaining sound financial structures to ensure business sustainability. Future studies are encouraged to explore qualitative aspects such as strategic innovation and governance transformation for more holistic insights. Keywords: Infrastructure, SOEs, Non-SOEs, Company Performance, Covid-19 Pandemic